Monocytic leukeima masquerading as a cutaneous lesion - Singh, Abhishek; Farheen, Shifa; Tripathi, Preeti; Sen, Arijit; Kashyap, Akriti (International Journal of Advances in Medicine, 2021)
Cutaneous lesions preceding a leukaemia are extremely rare and are referred to as ‘aleukaemic leukaemia cutis’. We present a case of acute monocytic leukaemia where skin infiltration of leukemic cells preceded any blood or bone marrow evidence of leukaemia. A 67-year-old woman presented with multiple cutaneous nodules all over the body of 3 months duration. Cutaneous examination showed multiple erythematous papules and plaques which were present over the face, trunk, extremities and back. Patient was evaluated at a nearby facility and was found to have normal blood parameters (TLC- 7130/cmm, N-57% L-34% M-09%). A skin biopsy done revealed infiltration of the dermis by atypical cells suggestive of a hematolymphoid malignancy. The patient was then shifted to our institution for tertiary care management. The blood counts over a period of one month showed gradually increasing TLC from an initial normal blood count to one showing absolute monocytosis (TLC-25500/cmm, AMC-3825/cmm) and finally abnormally high TLC (TLC-154050/cmm) with 79% monoblasts and promonocytes suggestive of acute leukaemia. A repeat skin biopsy again showed infiltration of atypical cells in the dermis. IHC done showed the atypical cells to be positive for monocytic markers (CD14, CD64). The patient had now started exhibiting systemic findings corroborating with the cutaneous lesions and skin biopsy. Bone marrow aspirate was hypercellular and showed replacement by monoblasts (82%). Cellular morphology was suggestive of AML-M5. Bone marrow biopsy showed a diffuse replacement of marrow by immature cells/blasts. Flow cytometry reports were also positive for monocytic markers. The patient was hence diagnosed as AML M5 with cutaneous metastasis/leukemia cutis and was immediately started on chemotherapy (3+7). Post induction phase, the patient was in remission and her skin lesions subsided. She was subsequently discharged and advised regular OPD follow up for maintenance therapy. This case is reported for its rarity.